Tough anti-swelling hydrogel with good biocompatibility and preparation method thereof

By introducing the hydrophilic copolymer PVA-co-PE into the hydrogel and preparing PHEA-(PVA-co-PE) hydrogel by rapid photo-initiation and immersion method, the problems of insufficient mechanical properties and low swelling resistance of traditional hydrogels are solved, and hydrogel preparation with good biocompatibility, strength and swelling resistance are achieved.

CN119751918AActive Publication Date: 2025-04-04SUZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411771418.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-04
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Traditional hydrogels are prone to deformation or rupture when subjected to external forces, and are prone to expand in a water environment, resulting in reduced mechanical strength and inflammation. The existing methods have problems such as complex preparation process or poor biocompatibility.

Method used

PHEA-(PVA-co-PE) hydrogel was prepared by using 2-hydroxyethylacrylate (HEA) as monomer, N,N’-methylenebisacrylamide (MBAA) as the crosslinker, 1-hydroxycyclohexylphenylketone (HPCK) as the photoinitiator, combined with poly(vinyl alcohol-co-ethylene) (PVA-co-PE) as the hydrophilic copolymer, and using two-step rapid photoinitiation and soaking method.

Benefits of technology

The prepared hydrogel has good biocompatibility, both strength and swelling resistance, and has a 146-fold increase in toughness and a modulus of 0.25MPa. It is suitable for use in different application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751918A_ABST
    Figure CN119751918A_ABST
Patent Text Reader

Abstract

The invention discloses tough anti-swelling hydrogel with good biocompatibility and a preparation method thereof.The preparation method comprises the steps that HEA serves as a monomer, MBAA serves as a cross-linking agent, HPCK serves as a photoinitiator and is dissolved in DMSO, and a PHEA precursor solution is prepared after ultrasonic treatment; the preparation method comprises the following steps: dissolving (PVA-co-PE) serving as a hydrophilic and hydrophobic copolymer in DMSO (Dimethylsulfoxide) through a heating and stirring method, and mixing to prepare a (PVA-co-PE)-DMSO solution; the preparation method comprises the following steps: mixing a (PVA-co-PE)-DMSO solution with a PHEA precursor solution, carrying out photocuring for a period of time, and soaking in water to obtain the PHEA-(PVA-co-PE) hydrogel with a micelle structure. The gel forming technology is simple, in the soaking process, due to the hydrophobic interaction of the copolymer, a micelle structure can be formed in the hydrogel through self-assembly, and the hydrophobic interaction is used for inhibiting swelling of a hydrophilic network and enhancing the mechanical property of the hydrogel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of hydrogel tissue engineering, and in particular relates to a strong and tough anti-swelling hydrogel with good biocompatibility and a preparation method thereof. Background Art

[0002] Hydrogel is a highly hydrated polymer material with a three-dimensional network structure that can absorb and retain a large amount of water. Hydrogels form in water and can maintain a certain shape, with the characteristics of high water content and controllability. Due to its unique properties, hydrogels have been widely used in many fields, such as tissue engineering, wound dressings, drug delivery, cell culture, etc.

[0003] However, traditional hydrogels generally have insufficient mechanical properties, especially when subjected to external forces, they are prone to deformation or rupture, which seriously limits the application of hydrogels. In order to overcome this problem, researchers have developed a variety of methods to improve the mechanical properties of hydrogels, including double network hydrogels, topological hydrogels, and nanostructured hydrogels.

[0004] In the above research on improving the mechanical properties of hydrogels, the following technical means have shown particular importance:

[0005] 1. Salting out: The aggregation state of hydrogel polymer chains is regulated by ions, thereby significantly improving the mechanical properties of hydrogels;

[0006] 2. Polyelectrolyte toughening: Use the Hofmeister effect of polyelectrolytes to strengthen hydrogels and improve mechanical properties.

[0007] Although the above methods can improve the mechanical properties of hydrogels, they also bring about the problem of reduced anti-swelling ability, which causes the hydrogel to swell easily in a water environment. Especially when used in vivo, this swelling will significantly reduce the mechanical strength of the hydrogel and exert pressure on adjacent tissues, causing inflammation. To solve this problem, researchers currently use the following technologies:

[0008] 1. Multiple cross-linking: by increasing the cross-linking points to form a denser network structure, the anti-swelling ability of the hydrogel can be improved;

[0009] 2. Ion complexation: Use the interaction between ions to enhance the mechanical properties and stability of hydrogels.

[0010] However, these methods may have problems such as complicated preparation process or poor biocompatibility. Therefore, developing a hydrogel with simple preparation method, good biocompatibility, strong toughness and anti-swelling properties is one of the technical problems to be solved urgently by those skilled in the art. Summary of the invention

[0011] In view of the problems existing in the prior art, the present invention provides a strong and tough anti-swelling hydrogel with good biocompatibility and a preparation method thereof, and utilizes the hydrophobic interaction of copolymers to complete the preparation of the strong and tough anti-swelling hydrogel, which not only has a simple process but also has good biocompatibility.

[0012] In order to solve the above technical problems, the present invention is implemented through the following technical solutions:

[0013] A method for preparing a strong and anti-swelling hydrogel with good biocompatibility comprises the following steps:

[0014] Step 1) 2-hydroxyethyl acrylate (HEA) is used as a monomer, N,N'-methylenebisacrylamide (MBAA) is used as a crosslinker, and 1-hydroxycyclohexyl phenyl ketone (HPCK) is used as a photoinitiator, which are dissolved in a certain volume of dimethyl sulfoxide (DMSO) according to a certain mass ratio, and a PHEA precursor solution is prepared after ultrasonic treatment for a period of time;

[0015] Step 2) dissolving a certain mass of poly(vinyl alcohol-co-ethylene) (PVA-co-PE) as a hydrophilic and hydrophobic copolymer in a certain mass of dimethyl sulfoxide (DMSO), and mixing for a period of time under certain temperature and stirring speed conditions to prepare a (PVA-co-PE)-DMSO solution with a specific mass fraction;

[0016] Step 3) A certain volume of the (PVA-co-PE)-DMSO solution prepared in step 2 is mixed with the PHEA precursor solution prepared in step 1, and after light curing for a period of time, it is immersed in water to finally obtain a PHEA-(PVA-co-PE) hydrogel with a micellar structure; the obtained PHEA-(PVA-co-PE) hydrogel has good biocompatibility, and has both strong toughness and anti-swelling properties.

[0017] Furthermore, in step 1, the mass of 2-hydroxyethyl acrylate is 4 g, the mass of N,N'-methylenebisacrylamide is 40 mg, the mass of 1-hydroxycyclohexyl phenyl ketone is 10 mg, and the volume of dimethyl sulfoxide is 2.5 mL.

[0018] Furthermore, in step 1, the ultrasonication time is 5 min.

[0019] Furthermore, in step 2, the temperature when poly(vinyl alcohol-co-ethylene) and dimethyl sulfoxide are mixed is 150° C., the stirring speed is 300 rpm, and the stirring time is 2 h.

[0020] Furthermore, in step 2, the mass fraction of the prepared (PVA-co-PE)-DMSO solution is 20%.

[0021] Further, in step 3, the volume of the (PVA-co-PE)-DMSO solution mixed with the PHEA precursor solution was 7.5 mL.

[0022] Furthermore, in step 3, the photocuring is performed by irradiating an ultraviolet lamp with a specific wavelength, so that the mixed solution of the (PVA-co-PE)-DMSO solution and the PHEA precursor solution forms a gel.

[0023] Furthermore, the wavelength of the ultraviolet light emitted by the ultraviolet lamp is 365nm.

[0024] Furthermore, in step 3, the light curing time is 1 minute.

[0025] A strong and tough anti-swelling hydrogel with good biocompatibility is prepared by adopting the preparation method of the strong and tough anti-swelling hydrogel with good biocompatibility. The prepared hydrogel has good biocompatibility and has both strength, toughness and anti-swelling properties.

[0026] The beneficial effects of the present invention are:

[0027] The present invention provides a method for simply preparing a hydrogel with excellent mechanical properties and good anti-swelling properties. The method introduces a hydrophilic and hydrophobic copolymer into the hydrogel, and forms a gel by a two-step method of rapid photoinitiation and immersion. During the immersion process, due to the hydrophobic interaction of the copolymer, the copolymer will self-assemble into a micelle structure inside the hydrogel, and the hydrophobic effect will be used to inhibit the swelling of the hydrophilic network and enhance the mechanical properties of the hydrogel, thereby meeting different application requirements.

[0028] When the (PVA-co-PE) content in the hydrogel of the present invention reaches 15wt%, the strength of the hydrogel can reach 0.65MPa, and the elongation at break reaches 320%. Compared with the hydrogel without adding (PVA-co-PE), the toughness of the hydrogel of the present invention is increased by 146 times, reaching 1.16MJ / m 3 , and the modulus reaches 0.25MPa.

[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. The specific implementation of the present invention is given in detail by the following embodiments and their accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0031] Figure 1 The flowchart is a method for preparing a strong and tough anti-swelling hydrogel with good biocompatibility of the present invention;

[0032] Figure 2 This is a SEM image of the PHEA-15% (PVA-co-PE) hydrogel after soaking in water in Test Example 1 of the present invention;

[0033] Figure 3 The stress-strain curves of PHEA hydrogel, PHEA-5% (PVA-co-PE) hydrogel, PHEA-10% (PVA-co-PE) hydrogel, and PHEA-15% (PVA-co-PE) hydrogel in Test Example 2 of the present invention;

[0034] Figure 4 The actual pictures, swelling ratio and water content result pictures of PHEA hydrogel, PHEA-5% (PVA-co-PE) hydrogel, PHEA-10% (PVA-co-PE) hydrogel and PHEA-15% (PVA-co-PE) hydrogel during the immersion process in Test Example 3 of the present invention are shown;

[0035] Figure 5 This is a graph showing the results of detecting the viability of 3T3 cells using the CCK8 method in Test Example 4 of the present invention;

[0036] Figure 6 This is a graph showing the swelling results of PHEA-15% (PVA-co-PE)-Bi hydrogel under the skin of mice in Test Example 5 of the present invention;

[0037] Figure 7 This is a tissue section image of the PHEA-15% (PVA-co-PE)-Bi hydrogel implanted subcutaneously in mice in Test Example 6 of the present invention. DETAILED DESCRIPTION

[0038] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings so that the purpose, features and advantages of the invention can be more clearly understood. It should be understood that the embodiments shown in the accompanying drawings are not intended to limit the scope of the present invention, but are only intended to illustrate the essential spirit of the technical solution of the present invention.

[0039] In the following description, certain specific details are set forth for the purpose of illustrating various disclosed embodiments to provide a thorough understanding of the various disclosed embodiments. However, those skilled in the relevant art will recognize that the embodiments may be practiced without one or more of these specific details. In other cases, well-known devices, structures, and techniques associated with the present application may not be shown or described in detail to avoid unnecessarily obscuring the description of the embodiments.

[0040] Unless the context requires otherwise, throughout the specification and claims, the word "comprise" and variations such as "include" and "have" should be construed in an open, inclusive sense, ie, should be interpreted as "including, but not limited to."

[0041] References throughout the specification to "one embodiment" or "an embodiment" indicate that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment. Thus, the appearances of "in one embodiment" or "in an embodiment" in various places throughout the specification are not necessarily all referring to the same embodiment. Furthermore, the particular features, structures, or characteristics may be combined in any manner in one or more embodiments.

[0042] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. It should be noted that the term "or" is generally employed in its sense including "and / or" unless the context clearly dictates otherwise.

[0043] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. Unless otherwise specified, the reagents and materials used in the present invention are commercially available.

[0044] The invention provides a strong and tough anti-swelling hydrogel with good biocompatibility. The hydrogel is mainly composed of a monomer: 2-hydroxyethyl acrylate (HEA), a hydrophilic and hydrophobic copolymer: poly(vinyl alcohol-co-ethylene) (PVA-co-PE), a cross-linking agent: N,N'-methylenebisacrylamide (MBAA) and a photoinitiator: 1-hydroxycyclohexyl phenyl ketone (HPCK).

[0045] See also Figure 1 As shown, the present invention also provides a method for preparing the strong and anti-swelling hydrogel with good biocompatibility, which specifically comprises the following steps:

[0046] Step 1) HEA, MBAA and HPCK are dissolved in a certain volume of dimethyl sulfoxide (DMSO) according to a certain mass ratio, and a PHEA precursor solution is prepared after ultrasonic treatment for a period of time;

[0047] Step 2) dissolving a certain mass of (PVA-co-PE) in a certain mass of dimethyl sulfoxide (DMSO), and mixing for a period of time under certain temperature and stirring speed conditions to obtain a (PVA-co-PE)-DMSO solution with a specific mass fraction;

[0048] Step 3) A certain volume of the (PVA-co-PE)-DMSO solution prepared in step 2 is mixed with the PHEA precursor solution prepared in step 1, and after light curing for a period of time, it is immersed in water to finally obtain a PHEA-(PVA-co-PE) hydrogel with a micellar structure; the obtained PHEA-(PVA-co-PE) hydrogel has good biocompatibility, and has both strong toughness and anti-swelling properties.

[0049] The preparation method, structure and performance of the hydrogel of the present invention are described in detail below through the following embodiments and test examples.

[0050] Example 1

[0051] Preparation of PHEA hydrogel:

[0052] First, 4 g of HEA, 40 mg of MBAA, and 10 mg of HPCK were dissolved in 10 mL of DMSO, and after ultrasonication for 5 min, 10 mL of PHEA precursor solution was prepared.

[0053] Then, 10 mL of the PHEA precursor solution was irradiated under an ultraviolet lamp with a wavelength of 365 nm to form a gel (irradiation time 1 min) to prepare a PHEA gel, which was then immersed in water.

[0054] Example 2

[0055] Preparation of PHEA-5% (PVA-co-PE) hydrogel:

[0056] First, 4 g of HEA, 40 mg of MBAA, and 10 mg of HPCK were dissolved in 7.5 mL of DMSO, and after ultrasonication for 5 min, 7.5 mL of PHEA precursor solution was prepared.

[0057] Then, 20 g of (PVA-co-PE) was placed in 80 g of DMSO, a magnetic bar was added, and the mixture was stirred for 2 h under a magnetic heating stirrer (temperature 150°C, rotation speed 300 rpm) to prepare a (PVA-co-PE)-DMSO solution with a mass fraction of 20%.

[0058] Finally, 2.5 mL of 20% (PVA-co-PE)-DMSO solution was measured and mixed with 7.5 mL of PHEA precursor solution, and irradiated under a UV lamp with a wavelength of 365 nm (irradiation time 1 min) to form a PHEA-5% (PVA-co-PE) hydrogel, which was then immersed in water.

[0059] Example 3

[0060] Preparation of PHEA-10% (PVA-co-PE) hydrogel:

[0061] First, 4 g of HEA, 40 mg of MBAA, and 10 mg of HPCK were dissolved in 5 mL of DMSO, and after ultrasonication for 5 min, 5 mL of PHEA precursor solution was prepared.

[0062] Then, 20 g of (PVA-co-PE) was placed in 80 g of DMSO, a magnetic bar was added, and the mixture was stirred for 2 h under a magnetic heating stirrer (temperature 150°C, rotation speed 300 rpm) to prepare a (PVA-co-PE)-DMSO solution with a mass fraction of 20%.

[0063] Finally, 5 mL of 20% (PVA-co-PE)-DMSO solution was measured and mixed with 5 mL of PHEA precursor solution, and irradiated under a UV lamp with a wavelength of 365 nm (irradiation time 1 min) to form PHEA-10% (PVA-co-PE) hydrogel, which was then immersed in water.

[0064] Example 4

[0065] Preparation of PHEA-15% (PVA-co-PE) hydrogel:

[0066] First, 4 g of HEA, 40 mg of MBAA, and 10 mg of HPCK were dissolved in 2.5 mL of DMSO, and after ultrasonication for 5 min, 2.5 mL of PHEA precursor solution was prepared.

[0067] Then, 20 g of (PVA-co-PE) was placed in 80 g of DMSO, a magnetic bar was added, and the mixture was stirred for 2 h under a magnetic heating stirrer (temperature 150°C, rotation speed 300 rpm) to prepare a (PVA-co-PE)-DMSO solution with a mass fraction of 20%.

[0068] Finally, 7.5 mL of 20% (PVA-co-PE)-DMSO solution was measured and mixed with 2.5 mL of PHEA precursor solution, and irradiated under a UV lamp with a wavelength of 365 nm (irradiation time 1 min) to form a PHEA-15% (PVA-co-PE) hydrogel, which was then immersed in water.

[0069] Example 5

[0070] Preparation of PHEA-15% (PVA-co-PE)-Bi hydrogel:

[0071] First, 4 g of HEA, 40 mg of MBAA, and 10 mg of HPCK were dissolved in 2.5 mL of DMSO, and 0.5 g of Bi was evenly dispersed therein using ultrasound. After ultrasound for 5 minutes, 2.5 mL of PHEA-Bi precursor solution was prepared.

[0072] Then, 20 g of (PVA-co-PE) was placed in 80 g of DMSO, a magnetic bar was added, and the mixture was stirred for 2 h under a magnetic heating stirrer (temperature 150°C, rotation speed 300 rpm) to prepare a (PVA-co-PE)-DMSO solution with a mass fraction of 20%.

[0073] Finally, 7.5 mL of 20% (PVA-co-PE)-DMSO solution was mixed with 2.5 mL of PHEA-Bi precursor solution and irradiated under a UV lamp with a wavelength of 365 nm (irradiation time 1 min) to form PHEA-15% (PVA-co-PE)-Bi hydrogel, which was then immersed in water.

[0074] Test Example 1

[0075] Observe the micelle structure inside the hydrogel after soaking in water:

[0076] The cross-sectional morphologies of the PHEA hydrogel prepared in Example 1 and the PHEA-15% (PVA-co-PE) hydrogel prepared in Example 4 were photographed using a cold field emission scanning electron microscope (Hitachi S-4700).

[0077] See also Figure 2 As shown, the images taken show that compared with PHEA hydrogel ( Figure 2 a), after soaking in water, a micellar structure composed of hydrophilic and hydrophobic copolymers was formed inside the PHEA-15% (PVA-co-PE) hydrogel ( Figure 2 b).

[0078] Test Example 2

[0079] Mechanical testing:

[0080] An electronic universal testing machine was used to perform tensile tests on the PHEA hydrogel, PHEA-5% (PVA-co-PE) hydrogel, PHEA-10% (PVA-co-PE) hydrogel, and PHEA-15% (PVA-co-PE) hydrogel prepared in Examples 1-4.

[0081] See also Figure 3 As shown in the figure, the test results show that after adding (PVA-co-PE), the strength (a), toughness and elastic modulus (b) of the hydrogel are significantly improved.

[0082] Test Example 3

[0083] Swelling behavior test and water content test:

[0084] The PHEA hydrogel, PHEA-5% (PVA-co-PE) hydrogel, PHEA-10% (PVA-co-PE) hydrogel, and PHEA-15% (PVA-co-PE) hydrogel prepared in Examples 1-4 were immersed in water for 6 h, 12 h, 24 h, and 48 h to test the swelling rate, and the water content of the hydrogel at swelling equilibrium was tested.

[0085] See also Figure 4 As shown, the test results show that as the content of the hydrophilic and hydrophobic copolymers increases, the anti-swelling ability of the hydrogel becomes stronger (a, b) and the water content becomes smaller (c).

[0086] Test Example 4

[0087] In vitro biocompatibility testing:

[0088] First, the PHEA-15% (PVA-co-PE) hydrogel prepared in Example 4 was sterilized with 75% ethanol for 3 h, and then immersed in sterilized PBS for 12 h (replaced every 4 h). Then, the hydrogel treated as above was immersed in DMEM culture medium for 24 h to obtain an leaching solution, which was diluted with culture medium to obtain a 50% leaching solution. 3T3 cells were cultured at 5×10 3 The cells were inoculated into a 96-well plate at a density of 100 cells and incubated at 37°C and 5% CO2 for 12 hours. The cells were allowed to adhere to the wall. The culture medium was then replaced with different hydrogel extracts. After incubation for 24 and 48 hours, 100 μL of blank culture medium (containing 10 μL of CCK-8 reagent) was added to each well and incubated at 37°C for another 30 minutes. The absorbance was measured at 450 nm using an ELISA reader to calculate cell viability.

[0089] See also Figure 5 As shown, it can be found from the test results that PHEA-15% (PVA-co-PE) hydrogel has good cell compatibility.

[0090] Test Example 5

[0091] In vivo anti-swelling phase test:

[0092] The PHEA-15% (PVA-co-PE)-Bi hydrogel prepared in Example 5 was made into a disc with a diameter of 5 mm, soaked in 75% ethanol for 3 hours, soaked in PBS for 12 hours, and then implanted subcutaneously in mice. The swelling of the hydrogel in mice was monitored using a small animal SPECT-CT imaging system on day 0, day 10, day 20, and day 30.

[0093] See also Figure 6 As shown, from the test results, it can be found that after being implanted subcutaneously in mice, the diameter of the PHEA-15% (PVA-co-PE)-Bi hydrogel did not change, indicating that the gel has good anti-swelling ability in vivo.

[0094] Test Example 6

[0095] In vivo biocompatibility testing:

[0096] Based on Test Example 5, HE tissue section staining was performed on the mouse skin in which the hydrogel was implanted subcutaneously 30 days later.

[0097] See also Figure 7 As shown, the test results showed that compared with the blank group (a), after gel implantation (b), the skin cell morphology did not change, and the surface hydrogel had good compatibility in vivo.

[0098] In summary, the present invention prepares PHEA-(PVA-co-PE) tough hydrogel by a rapid photoinitiated polymerization method, and controls the mechanical properties of the hydrogel by adjusting the content of (PVA-co-PE) to meet different application requirements. When the (PVA-co-PE) content reaches 15wt%, the strength of the hydrogel can reach 0.65MPa, and the elongation at break reaches 320%. Compared with the hydrogel without (PVA-co-PE), the toughness is increased by 146 times, reaching 1.16MJ / m 3 , and the modulus reaches 0.25MPa.

[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a strong and anti-swelling hydrogel with good biocompatibility, characterized in that: The following steps are involved: Step 1) 2-hydroxyethyl acrylate is used as a monomer, N,N'-methylenebisacrylamide is used as a crosslinker, and 1-hydroxycyclohexyl phenyl ketone is used as a photoinitiator, which are dissolved in a certain volume of dimethyl sulfoxide according to a certain mass ratio, and a PHEA precursor solution is prepared after ultrasonic treatment for a period of time; Step 2) dissolving a certain mass of poly(vinyl alcohol-co-ethylene) as a hydrophilic and hydrophobic copolymer in a certain mass of dimethyl sulfoxide, and mixing for a period of time under certain temperature and stirring speed conditions to prepare a (PVA-co-PE)-DMSO solution with a specific mass fraction; Step 3) A certain volume of the (PVA-co-PE)-DMSO solution prepared in step 2 is mixed with the PHEA precursor solution prepared in step 1, and after light curing for a period of time, it is immersed in water to finally obtain a PHEA-(PVA-co-PE) hydrogel with a micellar structure; the obtained PHEA-(PVA-co-PE) hydrogel has good biocompatibility, and has both strong toughness and anti-swelling properties.

2. The method for preparing a strong and anti-swelling hydrogel with good biocompatibility according to claim 1, characterized in that: In step 1, 4 g of 2-hydroxyethyl acrylate, 40 mg of N,N'-methylenebisacrylamide, 10 mg of 1-hydroxycyclohexyl phenyl ketone, and 2.5 mL of dimethyl sulfoxide were weighed.

3. The method for preparing a strong and anti-swelling hydrogel with good biocompatibility according to claim 1, characterized in that: In step 1, the ultrasonication time is 5 min.

4. The method for preparing a strong and anti-swelling hydrogel with good biocompatibility according to claim 1, characterized in that: In step 2, the temperature when poly(vinyl alcohol-co-ethylene) and dimethyl sulfoxide are mixed is 150° C., the stirring speed is 300 rpm, and the stirring time is 2 h.

5. The method for preparing a strong and anti-swelling hydrogel with good biocompatibility according to claim 1, characterized in that: In step 2, the mass fraction of the prepared (PVA-co-PE)-DMSO solution is 20%.

6. The method for preparing a strong and anti-swelling hydrogel with good biocompatibility according to claim 2, characterized in that: In step 3, the volume of the (PVA-co-PE)-DMSO solution used to mix with the PHEA precursor solution was 7.5 mL.

7. The method for preparing a strong and anti-swelling hydrogel with good biocompatibility according to claim 1, characterized in that: In step 3, the photocuring is performed by irradiating an ultraviolet lamp with a specific wavelength, so that the mixed solution of the (PVA-co-PE)-DMSO solution and the PHEA precursor solution forms a gel.

8. The method for preparing a strong and anti-swelling hydrogel with good biocompatibility according to claim 7, characterized in that: The wavelength of the ultraviolet light emitted by the ultraviolet lamp is 365nm.

9. The method for preparing a strong and anti-swelling hydrogel with good biocompatibility according to claim 1, characterized in that: In step 3, the light curing time is 1 minute.

10. A strong and anti-swelling hydrogel with good biocompatibility, characterized in that: The hydrogel is prepared by the method for preparing a strong, tough and anti-swelling hydrogel with good biocompatibility as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Manufacturing method and application of PVA-HEA ultraviolet three-dimensional dose meter

    CN104877147A

  • Anti-swelling tough hydrogel and preparation method thereof

    CN115368588A

  • Micro-phase separation tough hydrogel with excellent swelling resistance and preparation method thereof

    CN116925392A

  • Creep resistant, highly lubricious, tough, and ionic hydrogels including PVA-paamps hydrogels

    US20110054622A1